Preclinical update on regulation of intracranial pressure in relation to idiopathic intracranial hypertension - Sajedeh Eftekhari; Connar Stanley James Westgate; Maria Schmidt Uldall; Rigmor Hoejland Jensen (Fluids and Barriers of the CNS, 2019)
Abstract Background Elevated intracranial pressure (ICP) is observed in association with a range of brain disorders. One of these challenging disorders is idiopathic intracranial hypertension (IIH), characterized by raised ICP of unknown cause with significant morbidity and limited therapeutic options. In this review, special focus is put on the preclinical research performed in order to understand the pathophysiology behind ICP regulation and IIH. This includes cerebrospinal fluid dynamics, molecular mechanisms underlying disturbances in brain fluids leading to elevated ICP, role of obesity in IIH, development of an IIH model and ICP measurements in rodents. The review also discusses existing and new drug targets for IIH that have been evaluated in vivo. Conclusions ICP monitoring in rodents is challenging and different methods have been applied. Some of these methods are invasive, depend on use of anesthesia and only allow short-term monitoring. Long-term ICP recordings are needed to study IIH but existing methods are hampered by several limitations. As obesity is one of the most common risk factors for IIH, a rodent obese model has been developed that mimics some key aspects of IIH. The most commonly used drugs for IIH have been evaluated in vivo for their efficacy at lowering ICP in the existing animal models. These studies suggest these drugs, including acetazolamide, might have limited or no reducing effect on ICP. Two drug targets that can impact ICP in healthy rodents are topiramate and a glucagon-like peptide-1 receptor (GLP-1R) agonist. However, it remains to evaluate their effect in an IIH model with more precise and valid ICP monitoring system. Therefore, continued evaluation in the preclinical research with refined tools is of great importance to further understand the pathophysiology behind disorders with raised ICP and to explore new drug targets.